Development of Virtual Map Learning Media Based on Augmented Reality to Increase the Learning Interest of Grade IV Students - Fatinah, Titin; Setyawan, Agung; Citrawati, Tyasmiarni; Fajrin, Nilamsari Damayanti (Yayasan Citra Dharma Cindekia, 2024)
In the digital era, ICT advancements have significantly influenced education, enhancing students' learning experiences. This study focuses on developing Augmented Reality (AR)-based learning media for fourth-grade Indonesian Language students at SDN Larangan Luar 2, Pamekasan. Using a constructivist approach, it addresses students' low interest and motivation in learning Indonesian and emphasizes the teacher’s role as a facilitator. The Research and Development (RnD) approach follows the ADDIE framework—analysis, design, development, implementation, and evaluation. Seventeen students participated in observations and interviews to assess their learning characteristics and needs. Findings indicate that traditional learning methods often render students passive, necessitating innovative teaching strategies. The study introduces an AR-based Virtual Map that merges digital objects with real-world elements to create an interactive learning experience. Validation results confirmed the media’s effectiveness, with high scores from learning design experts (86%), subject matter experts (84%), and instructional material experts (92%). The research highlights AR's potential in increasing students’ interest and motivation in learning Indonesian. It also serves as a reference for educators and developers in designing engaging and interactive teaching methods, ultimately contributing to more effective learning experiences.